Co-ordination media in cross-national networks of small and medium-sized enterprises - Ralph-Elmar Lungwitz; Peter Le; Sebastian Campagna (Journal for East European Management Studies, 2006)
Not only large corporations but also SMEs increasingly organise into crossborder networks, in order to benefit from the advantages of international division of labour. As regards the co-ordination of network activities it makes sense to distinguish between the role of social co-ordination media and the factual and temporal co-ordination of network activities. Social co-ordination media are geared to the generation of mutual reliability. Their mode of operating is closely linked to the internal power structures of the networks. – – Nicht nur Großunternehmen, sondern auch Kleine und Mittlere Unternehmen schließen sich in wachsendem Maße zu grenzüberschreitenden Netzwerken zusammen, um die Vorteile der internationalen Arbeitsteilung zu nutzen. Hinsichtlich der Koordinierung von Netzwerksaktivitäten macht es Sinn, zwischen dem Wirken sozialer Koordinierungsmedien und der sachlichzeitlichen Koordinierung von Teilaktivitäten zu unterscheiden. Die sozialen Koordinierungsmedien sind auf die wechselseitige Generierung von Verlässlichkeit (Relianz) ausgerichtet. Ihre Wirkungsweise hängt mit charakteristischen Machtstrukturen innerhalb der Netzwerke zusammen.
Keywords: 650; SMEs; Cross-border Networks; Co-ordination Media